2017
DOI: 10.1093/mmy/myx087
|View full text |Cite
|
Sign up to set email alerts
|

Itraconazole in combination with neutrophil depletion reduces the expression of genes related to pulmonary fibrosis in an experimental model of paracoccidioidomycosis

Abstract: Itraconazole (ITC) is the drug of choice for treating paracoccidioidomycosis (PCM); nonetheless, patients with the chronic form of this mycosis develop fibrosis, a residual pulmonary abnormality, even after treatment. Recently, we observed that the depletion of neutrophils with a specific monoclonal antibody (mAb-anti-Ly6G) during the chronic stages of PCM was associated with a decrease in the fungal burden, the inflammatory response and a reduction of fibrosis. Herein, we aimed to evaluate the effect of ITC i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…25 TIMP-1 and TIMP-2 are mainly expressed in epithelial cells, and TIMP-1 gene expression was up-regulated in pulmonary fibrosis in vivo. 45 TGF-β1 modulated the homeostasis between MMPs and TIMPs through p38 MAPK and ERK1/2 in breast cancer cells. 46 In current study, whether the gene or protein levels of TIMP-1 and TIMP-2 were all dose-dependent increases treated with Nano NiO.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…25 TIMP-1 and TIMP-2 are mainly expressed in epithelial cells, and TIMP-1 gene expression was up-regulated in pulmonary fibrosis in vivo. 45 TGF-β1 modulated the homeostasis between MMPs and TIMPs through p38 MAPK and ERK1/2 in breast cancer cells. 46 In current study, whether the gene or protein levels of TIMP-1 and TIMP-2 were all dose-dependent increases treated with Nano NiO.…”
Section: Discussionmentioning
confidence: 97%
“…It has been observed that the increased expression of MMP‐1 and MMP‐9 in idiopathic pulmonary fibrosis was related to the changes of TIMP‐1 and TIMP‐2 in A549 cells . TIMP‐1 and TIMP‐2 are mainly expressed in epithelial cells, and TIMP‐1 gene expression was up‐regulated in pulmonary fibrosis in vivo . TGF‐β1 modulated the homeostasis between MMPs and TIMPs through p38 MAPK and ERK1/2 in breast cancer cells .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it also diminished the number of inflammatory cells—including neutrophils—in the lungs of mice infected with P . brasiliensis [ 27 ]. In the present study, it was observed that the ITC regulates the expression of the MMP-15 and TIMP-2 genes that have been recognized as inducers of pulmonary fibrosis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models of PCM have allowed characterization of the mechanisms involved in the development of pulmonary fibrosis, and evaluate diverse strategies to treat it. Thus, combined therapies including pentoxifylline plus ITC [ 26 ], or an anti- neutrophil monoclonal antibody alone or in combination with ITC [ 27 , 28 ], have showed that such treatment strategies reduced substantially the PF. However, the potential risk for using immunosuppressive drugs or biological agents, mainly in host with other unknown latent infections, should be considered [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The immunization with P10 in association with conventional drugs resulted in the absence of granulomas and areas with very few or undetectable yeast cells (37). Similarly, Naranjo and collaborators combined itraconazole-pentoxifylline treatment to reduce lung fibrosis in the murine model of PCM (36), and Puerta-Arias and collaborators were able to reduce the infection and pulmonary fibrosis with a combination of ITZ and monoclonal antibody against neutrophils (38).…”
Section: Discussionmentioning
confidence: 99%